The Importance of Spacing and Thinning to Improve Productivity and Wood Properties of Clonal Teak Plantation - Widiyatno; Aris Wibowo; Nur Laily Anisa; Dian Novitasari; Rika Bela Rahmawati; Sawitri; Sigit Sunarta; Suryo Hardiwinoto; Naoki Tani (Jurnal Sylva Lestari, 2026)
Clonal teak in Indonesia was produced through a tree improvement program that selected superior mother trees. These clones showed high growth and could produce more than 200 m3/ha in 20 years after planting. The silvicultural treatment could improve the growth of clonal teak through spacing arrangements and thinning. However, studies combining the effects of spacing and thinning to improve forest productivity in clonal teak plantations remain limited. Therefore, this study aims to determine the effect of different spacing and thinning intensity on the productivity of a 13-year-old clonal teak plantation. A nested randomized complete block design was used with 3 blocks as replication. The treatment comprised 4 spacing types: 3 m x 3 m, 6 m x 2 m, 8 m x 2 m, and 10 m x 2 m. Meanwhile, 3 thinning intensities were nested within each spacing treatment: 0% (control), 25% (medium thinning), and 50% (heavy thinning). The results showed that at the age of 13 years old, spacing treatment affected the development of diameter at breast height (DBH), mean annual diameter increment (MADI), tree bole height (TBH), crown diameter (CD), canopy openness (CO), competition index (CI), and pilodyn penetration (PP) (p < 0.05). Spacing treatment did not affect height (H), volume (Vol), and stress wave velocity (SWV) (p > 0.05). The best spacing to improve DBH, MADI, CD, CO, and PP was 10 m x 2 m, yielding 29.68 cm, 2.30 cm/year, 5.18 m, 54.84%, and 20.21 mm, respectively. Additionally, thinning intensity, nested within spacing treatment, significantly affected DBH, MADI, Vol, CO, and CI (p < 0.05). In conclusion, a combination of spacing 10 m x 2 m and thinning intensity 50% is recommended to increase forest productivity in a clonal teak plantation. Keywords: clonal teak, forest productivity, spacing, thinning intensity, wood properties